2021
DOI: 10.1016/j.braindev.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in Angelman syndrome: A scoping review

Abstract: Angelman Syndrome (AS) is characterized by severe developmental delays including marked speech impairment, movement abnormalities(ataxia, tremor), and unique behaviors such as frequent laughter and is caused by dysfunctional maternal UBE3A gene (maternal 15q11-13 deletions, maternal specific UBE3A mutation, uniparental disomy, and imprinting defect). Intractable epileptic seizures since early childhood with characteristic EEG abnormalities are present in 80-90% patients with AS. Underlying pathophysiology may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 88 publications
3
20
0
Order By: Relevance
“…Many aspects of the case presented here are consistent with previous reports of AS patients with the underlying cause of paternal UPD ( Lossie et al, 2001 ; Poyatos et al, 2002 ; Thompson and Bolton, 2003 ; Tsai et al, 2004 ; Varela et al, 2004 ; Saitoh et al, 2005 ; Bonati et al, 2007 ; Depienne et al, 2009 ; Horváth et al, 2013 ; Luk and Lo, 2016 ), who generally had a lower prevalence of seizure, normal head circumference and absence of hypopigmentation ( Lossie et al, 2001 ; Depienne et al, 2009 ; Horváth et al, 2013 ; Samanta, 2021 ). AS patients with UPD also have a higher risk of obesity than deletion type ( Lossie et al, 2001 ; Poyatos et al, 2002 ; Varela et al, 2004 ; Saitoh et al, 2005 ; Brennan et al, 2015 ; Luk and Lo, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…Many aspects of the case presented here are consistent with previous reports of AS patients with the underlying cause of paternal UPD ( Lossie et al, 2001 ; Poyatos et al, 2002 ; Thompson and Bolton, 2003 ; Tsai et al, 2004 ; Varela et al, 2004 ; Saitoh et al, 2005 ; Bonati et al, 2007 ; Depienne et al, 2009 ; Horváth et al, 2013 ; Luk and Lo, 2016 ), who generally had a lower prevalence of seizure, normal head circumference and absence of hypopigmentation ( Lossie et al, 2001 ; Depienne et al, 2009 ; Horváth et al, 2013 ; Samanta, 2021 ). AS patients with UPD also have a higher risk of obesity than deletion type ( Lossie et al, 2001 ; Poyatos et al, 2002 ; Varela et al, 2004 ; Saitoh et al, 2005 ; Brennan et al, 2015 ; Luk and Lo, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…Other patients with multifocal or generalized epilepsy and children with epileptic encephalopathies benefited from genetic testing (a more defined pathway for genetic testing in the clinic can further improve the workflow), medical therapy, neuromodulation, dietary therapy, and palliative surgery. [16,[28][29][30][31]] Interestingly, we observed significantly more patients receiving a recommendation for VNS compared to dietary therapy. It is unclear if regular access of a neurosurgeon in the clinic caused a bias recommendation toward VNS.…”
Section: Discussionmentioning
confidence: 86%
“…Seizure and microcephaly have been reported to be more common and severe in the deletion group [ 53 , 63 , 64 , 65 ]. The deletion subtype is associated with the most severe epilepsy phenotype; in contrast, non-deletion patients may have relatively late-onset seizures [ 64 , 66 ]. Mertz et al found that children with a deletion type had significantly reduced developmental age regarding visual perception, receptive language, and expressive language compared with those having a UBE3A mutation and pUPD [ 58 ].…”
Section: Genotype–phenotype Correlation In Angelman Syndromementioning
confidence: 99%
“…Compared to the patients with deletion type, patients with paternal UPD have a much lower prevalence of epilepsy, better development and expressive language ability; some patients may even speak 2–7 words [ 58 , 59 ]. The UPD subtype is also associated with the lowest frequency of epilepsy and exhibits the least severe epilepsy phenotype [ 66 ]. Varela et al found that swallowing disorders, hypotonia, and microcephaly in the UPD type are less severe than those in the deletion type [ 57 ].…”
Section: Genotype–phenotype Correlation In Angelman Syndromementioning
confidence: 99%